Ochrona różnorodności biologicznej w systemach certyfikacji FSC i PEFC a gospodarka leśna w Polsce - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2010)
This paper gives an analysis of the relative merits of the FSC and PEFC certification systems, which are in force in Poland. The biodiversity protection provided by implementation of the two schemes during forest management is assessed with respect to: the preference for natural forest regeneration, the introduction of alien species and genetically modified organisms, the preservation of dead wood and hollow trees in forests, and the use of low-impact technologies in forest work. The problem of financing more-ecological forest management is also discussed. Both certification systems consider biodiversity protection on a large scale but with different precisions and restrictiveness. The implementation of certification systems requires the simultaneous development of scientific research and ecological education throughout society.